Correlation Between Thermal Diffusivity Variation and Quality of Cold Preserved Fish - F.A Ansari; K.A Abbas; M.M.H Megat Ahmad (ASEAN Journal on Science and Technology for Development, 2004)
The present paper deals with establishment of correlation between thermal behaviour and quality of cold preserved fish. Experiments were designed and transient temperature-time variations were recorded at the center and other three equidistant locations during air blast cooling of slab shaped pieces of fresh water fish. A number of pieces from the same lot were cold preserved at 3°C for a period of 28 days and experiments were repeated daily. Time-temperature records were used to determine thermal diffusivity of each sample using the empirical approach of the first author, reported elsewhere. It was observed that the measured thermal diffusivity increased up to 14 days and then stayed approximately constant up to the end of the preservation period (28 days). According to the reported literature, it was found that the shelf life of fish preserved at 3°C is 14 days. Regression analysis was made to develop an empirical correlation between thermal diffusivity and preservation time of the fish under investigation.